"Die Tribute von Panem" - zur Adaption des ersten tesli der Roman trilogie von Suzanne Collins = "The Hunger Games" - on the ada ptation of the first part of Suzanne Collins`s trillogy - Hernik-Młodzianowska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper focuses on the relation between the literary original and the film version of the successfulall-ages novel "The Hunger Games" by Suzanne Collins. The main issue is not the quality of the film inrelation to the novel. The paper focuses basically on the question of cinematic techniques which wereused to replace the narrative techniques on the movie screen. The paper compares the micro- andmacrostructure of both film and novel to show the differences between them. The author analysesthe role of the narrator in the novel to show how he can be "replaced" in the film. The paper alsoanalyses the form of the adaptation of the first part of "The Hunger Games".
Keywords: Collins, Suzane (1962- ); adaptacja filmowa